Journalism is changing – and what about journalism ethics? - Fidalgo, Joaquim (2013)
Major changes have been challenging journalism in the last two decades, in the context of the ‘digital age’. The technological possibilities developed in the ‘information society’, together with the social and cultural trend for more participation, opened this field to new actors, which caused professional journalists to lose their traditional monopoly of searching, gathering, editing and diffusing news in the public sphere. At the same time, these new possibilities of communicating are increasingly forcing the old actors to play new roles in the media. The digital techniques and the Internet gave birth to a big diversity of new media and of new forms of dealing with journalism and public information. ‘Citizen journalism’, ‘participatory journalism’, ‘user-generated content’, ‘crowdsourcing’, ‘weblogs’,‘ Twitter’, ‘Facebook’, etc., are words and expressions rather common these days, all of them somehow calling the attention to the fact that journalism-as-a-professional-activity seems to coexist more and more with various forms of journalism-as-a-civic-activity, performed by very different people, under very different conditions and with very different levels of involvement and expertise. As a consequence, questions are being raised about the ethical implications of this new scenario, both in what regards the activity of professional journalists in new (online) media and the active commitment of ‘laypersons’ in the process of gathering, editing and diffusing information. In this paper we will try to analyze and to discuss these questions, with reference, among others, to Eliot Freidson (2004) and his distinction between ‘practice ethics’ and ‘institutional ethics’. Furthermore, we’ll try to discuss what really makes journalism distinctive from other practices that nowadays coexist with it in the public sphere, strongly increasing the possibilities of communication between people but not necessarily following the purposes of public interest and of civic democratic participation. In this context, the concept of journalism seems to ask for a clearer definition, and so do the roles to be played by journalists in the more complex (but also more stimulating) media environment we are dealing with in contemporary societies.